Food Safety Counseling at Home Industry in Moiso Village for Assistance with Permit Number PIRT (Pangan Industri Rumah Tangga) - Muhamad Saleh, Erna Rusliana; Ibrahim, Abu Rahmat; Juharni, Juharni (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2022)
The home industry for coconut jam and VCO in Moiso village does not yet have a PIRT number so that the marketing of these two products is still limited. This is because they do not have knowledge related to PIRT management. Assistance is needed from parties who understand this. In the management of PIRT, there are stages of food safety education. Food safety education was attended by the home industry coordinator and his team. In this counseling material was presented on food safety, food packaging and labeling, the application of CPPB and food processing technology. There are pre-test and post-test at the beginning and end of the activity to assess participants' mastery before and after being given food safety education. The results of the counseling show that home industries are entitled to PIRT with several improvements to level 1 or 2. Several things need to be improved, including improving the position of the production site so that it is not close to the WC, storage areas for materials and tools to be more organized, sources of clean water for more production guaranteed continuity. Moiso's home industry has received a Food Safety certificate from the West Halmahera Health Office.